Isorhamnetin Inhibits Liver Fibrosis by Reducing Autophagy and Inhibiting Extracellular Matrix Formation via the TGF-β1/Smad3 and TGF-β1/p38 MAPK Pathways. (31st July 2019) - Liu, Ning; Feng, Jiao; Lu, Xiya; Yao, Zhilu; Liu, Qing; Lv, Yang; Han, Yuru; Deng, Jingfan; Zhou, Yingqun
Abstract : Objective . Liver fibrosis is a consequence of wound-healing responses to chronic liver insult and may progress to liver cirrhosis if not controlled. This study investigated the protection against liver fibrosis by isorhamnetin. Methods . Mouse models of hepatic fibrosis were established by intraperitoneal injection of carbon tetrachloride (CCl4 ) or bile duct ligation (BDL). Isorhamnetin 10 or 30 mg/kg was administered by gavage 5 days per week for 8 weeks in the CCl4 model and for 2 weeks in the BDL model. Protein and mRNA expressions were assayed by western blotting, immunohistochemistry, and quantitative real-time polymerase chain reaction. Results . Isorhamnetin significantly inhibited liver fibrosis in both models, inhibiting hepatic stellate cell (HSC) activation, extracellular matrix (ECM) deposition, and autophagy. The effects were associated with downregulation of transforming growth factor β 1 (TGF- β 1) mediation of Smad3 and p38 mitogen-activated protein kinase (MAPK) signaling pathways. Conclusion . Isorhamnetin protected against liver fibrosis by reducing ECM formation and autophagy via inhibition of TGF- β 1-mediated Smad3 and p38 MAPK signaling pathways.